A CENTURY OF ARAB-AMERICANS: FROM IMMIGRANTS TO CITIZENS - Al-Matrafi, Huda B. (PEOPLE: International Journal of Social Sciences, 2017)
The United States of America has been the land of immigration that experienced successive waves of immigration since the 17th century. The Arab immigration is a part of that history. This paper looks at the history of Arab immigrants in the USA. It illustrates how these immigrants became American citizens within a century focusing on political, social, and economic factors that have pushed these immigrants out of their original homelands. It draws attention to the distinctive waves of the Arab immigration and how each wave had contributed in the formation of an Arab-American identity. Most of the previous researches on Arab-Americans concentrate on their literary works examining issues such as hybridization, 'double consciousness', and the feeling of being "out of place". This paper, however, introduces the idea of how the Arab-Americans, through different generations and circumstances, have achieved their goal in creating an official existence that formed 'a nation within a nation', despite the fact that they have been shattered and traumatized by social and political issues both in the 20th century and the new millennium. Hence, this paper highlights the importance of history in transforming the Arab-American identity from an Arab immigrant to an American citizen. However, it concludes that this new nation might return to being a nation of immigrants at the end of the road with the new presidency and its extreme chauvinistic politics.